Partial-norm-constrained sparse recovery algorithm and its application on single carrier underwater-acoustic-data telemetry - Feiyun WU; Kunde YANG; Feng TONG (Tongxin xuebao)
To solve the problem of single carrier underwater-acoustic-data telemetry,compressive sensing (CS) provides competitive performance of compression and recovery with low energy consumption.The primary objective of CS is to minimize the l0norm,which is an NP hard problem.Hence,the common methods were transferred to minimize l1norm.However,l1norm minimization provided a limited accuracy.A partial-norm-constraint (PNC) based sparse signal recovery method was derived,which adopted PNC as a zero attraction in a Lagrange method,to distribute the soft threshold for the non-zero taps.The proposed method is used for at-sea data telemetry.Combining with DCT,the proposed method improves the recovery accuracy.